The whistleblower : sex trafficking, military contractors, and one woman's fight for justice - Bolkovac, Kathryn; Lynn, Cari. (New York : Palgrave Macmillan, 2011)
"When Nebraska police officer and divorced mother of three Kathryn Bolkovac saw a recruiting announcement for private military contractor DynCorp International, she applied and was hired. Good money, world travel, and the chance to help rebuild a war-torn country sounded like the perfect job. Bolkovac was shipped out to Bosnia, where DynCorp had been contracted to support the UN peacekeeping mission. She was assigned as a human rights investigator, heading the gender affairs unit. The lack of proper training sounded the first alarm bell, but once she arrived in Sarajevo, she found out that things were a lot worse. At great risk to her personal safety, she began to unravel the ugly truth about officers involved in human trafficking and forced prostitution and their connections to private mercenary contractors, the UN, and the U.S. State Department. After bringing this evidence to light, Bolkovac was demoted, threatened with bodily harm, fired, and ultimately forced to flee the country under cover of darkness--bringing the incriminating documents with her. Thanks to the evidence she collected, she won a lawsuit against DynCorp, finally exposing them for what they were. This is her story and the story of the women left behind."--
Includes bibliographical references and index.
Keywords: Bolkovac, Kathryn; Whistle blowing -- Bosnia and Hercegovina; Whistle blowing -- United States; Human trafficking -- Bosnia and Hercegovina; Private military companies -- Bosnia and Hercegovina